Antimicrobial lignans derived from the roots of Streblus asper. (December 2016) - Nie, Hui; Guan, Xin-Lan; Li, Jian; Zhang, Yan-Jun; He, Rui-Jie; Huang, Yan; Liu, Bu-Ming; Zhou, De-Xiong; Deng, Sheng-Ping; Chen, Huang-Can; Yang, Rui-Yun; Li, Jun
Graphical abstract: Highlights: Ten compounds including four new ones were isolated from its root. Four new lignans structures were characterized by extensive spectroscopic analyses and comparison with published data. Six lignans showed good antimicrobial activity. Abstract: Four new lignans, (7′ R, 8′ S )-4, 4'-Dimethoxy-strebluslignanol (1 ), 3'-Hydroxy-isostrebluslignaldehyde (2 ), 3, 3'-Methylene-bis(4-hydroxybenzaldehyde) (3 ), and 4-Methoxy-isomagnaldehyde (4 ), and six known lignans (5 –10), were isolated from the roots of Streblus asper . The structures of these molecules were elucidated through various spectroscopic methods of analysis, including 1D and 2D NMR. The stereochemistry at the chiral centres was determined using the CD spectrum and from coupling constant and optical rotation data. Compounds1–6 showed good antimicrobial activity against Saccharomyces cerevisiae (ATCC 9763), Bacillus subtilis (ATCC 6633), Pseudomonas aeruginosa (ATCC 9027), Escherichia coli (ATCC 11775), and Staphylococcus aureus (ATCC 25923), with MIC values ranging from 0.0150 to 0.0940 μM.